An algorithm for 2D radar to ESM correlation based on fuzzy data association - Gu En-Ting; Tan Yu-Lei; Yu Zhi-Cheng; Zhou Xi-Wa; Yu Yong (2011 Cross Strait Triple-Regional Radio Science and Wireless Technology Conference, 2011)
The radar to Electronic Support Measurement (ESM) correlation problem is an important subject of military multi-sensory data fusion. This paper gives a new algorithm by using fuzzy data association algorithm. The simulation results demonstrate that the algorithm is both effective and practical.